Pengaruh Entrepreneurial Education terhadap Entrepreneurial Intention Pada Siswa SMK Bisnis Daring dan Pemasaran (BDP) - Reffandi, Krista Suci; Sulistyowati, Raya (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2024)
The rapid population growth raises various problems, one of which is increasing the number of unemployed. Entrepreneurship is a solution to create jobs, thus it requires interpretation related to entrepreneurial attitudes, intentions and actions. This study aims to analyze the effect of entrepreneurial education on entrepreneurial intention of Online Business and Marketing Vocational School Students in Surabaya. This research used quantitative methods with a purposive sampling technique. The population in this study were Online Business and Marketing Vocational School students at Surabaya State Vocational School with a research sample of 267 respondents. The data analysis technique used Structural Equation Modeling Partial Least Squares (SEM-PLS) with the Smart-PLS 3 tool. The test model in this study includes the outer model, inner model and hypothesis testing. The results of the study show that entrepreneurial education has a positive and significant effect on entrepreneurial intention.